Surviving the Unpleasant : Hope of the Child of Divorce - Nur'aini Azizah; Sarbini Sarbini; Tahrir Tahrir (PSIKODIMENSIA, 2020)
Divorced family may prone to stress and experience hopelessness. This study aims to explore the development of hope of a student from divorced family. This study used case study method with qualitative approach and interviewed an undergraduate student in an Islamic university in Bandung. The findings show that the participant experienced the development of hope despite its prior negative experience with the family. The participant was able to describe her goals in detail. Her effort to achieve the goals indicates the pathways aspect through her actions related to the goals. The agency aspect was expressed through her motivation to perform more than others. She usually wrote down the goals and attempted to obtain various social supports. One main factor influencing her hope was the relationship with the caregiver, her mother.